2016
DOI: 10.1109/tbme.2016.2600637
|View full text |Cite
|
Sign up to set email alerts
|

A Method for Intertemporal Functional-Domain Connectivity Analysis: Application to Schizophrenia Reveals Distorted Directional Information Flow

Abstract: Objective We introduce a method for analyzing dynamically changing fMRI brain network connectivity estimates as they vary within and between broad functional domains. The method captures evidence of intertemporal directionality in cross joint functional domain influence, and extends standard whole-brain dynamic network connectivity approaches into additional functionally meaningful dimensions by evaluating transition probabilities between clustered intra-domain and inter-domain connectivity patterns. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 21 publications
3
19
0
Order By: Relevance
“…We then evaluated the assumptions underlying naive network-based models, in particular the assumptions that brain networks are independent and stable. Inconsistent with the canonical model of localized and temporally stable networks (and consistent with the dynamic connectivity literature) 32,41 , we found that canonical brain networks are temporally decomposable into an array of possible connectivity states. Moreover, each local connectivity state also provides information about the global state of the entire brain.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…We then evaluated the assumptions underlying naive network-based models, in particular the assumptions that brain networks are independent and stable. Inconsistent with the canonical model of localized and temporally stable networks (and consistent with the dynamic connectivity literature) 32,41 , we found that canonical brain networks are temporally decomposable into an array of possible connectivity states. Moreover, each local connectivity state also provides information about the global state of the entire brain.…”
Section: Discussionsupporting
confidence: 87%
“…Inconsistent with models that suggest uniformity of brain networks over time, and consistent with recent results using dynamic functional connectivity 41 , we found that networks could be resolved temporally into NC-states. This result parallels and extends the observation that the whole connectome can be resolved temporally into whole-brain states 32 .…”
Section: Each Canonical Network Is Resolvable Into a Set Of Network Csupporting
confidence: 91%
See 2 more Smart Citations
“…64 New methods being developed to optimize across multiple domains have yielded some interesting results. 65,66 Fig. 11 shows an example of estimated joint functional domains compared with the static (averaged) FNC matrix.…”
Section: Number 8: Labeling the Independent Component Analysis Componmentioning
confidence: 99%